CONSUMER PROTECTION LAW ON VEHICLE LEASING AGREEMENT IN INDONESIA - Firda Ayu Ramadhani; Gianto Al Imron (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article aims to study the legal protection for the consumers of motor vehicles in regards to their financing agreement. The study uses the statute, conceptual, and contractual approach. The results of the research show that the act of forced effort carried out by creditors against motor vehicles as objects of fiduciary security can be said as an unlawful act, because the execution carried out is not in accordance with the method regulated in Article 29 of the Fiduciary Guarantee Act. The purpose of this study is to analyze the status of motor vehicles ownership in a consumer financing agreement when a bad credit occurs, and to analyze the execution of a motor vehicles caused by a consumer default. This study concludes that legal protection should be improved, consumers should be able to be more careful in choosing the services of motor creditors.